Institutional Injustice and Authorial Critique in Kathryn Stockett's The Help - Jourdan Eden Nico; Erna Cahyawati; Imam Basuki; Ghanesya Hari Murti (Pusat Studi Gender Universitas Jember, 2025)
This research aims to analyze how Kathryn Stockett's The Help represents systemic racism and author's critical position towards the racial injustice issue within the novel. This research applies two theories: the representation by Stuart Hall and the theory of systemic racism by Joe. R. Feagin. This research applies a qualitative method with a narrative text analysis approach. The results of this study show that systemic racism plays a role in the level of labor exploitation, economic discrimination, social inequality, and oppressive social norms. Thus, the author's position also shows an effort to criticize the unjust system. However, she notes there are still some limitations since white characters are still central to hold primary control. This study concludes that literary works can function as a medium to voice social criticism of racism, while reflecting the complexity of the author's position in shaping representations of racial injustice.